After McDonaldization : mission, ministry, and Christian discipleship in an age of uncertainty - Drane, John William (Grand Rapids, MI : Baker Academic, 2008)
In his earlier The McDonaldization of the Church, noted author John Drane critiqued current church trends toward "fast food" spirituality while offering suggestions for change. In his long-awaited sequel, After McDonaldization, Drane addresses key questions for Western Christianity in a global context. He argues that increasing numbers of people are turning to "spirituality" even while church attendance has continued to decline in the US and Europe, and that the continuing impact of globalization and consumerism has been joined by a post-9/11 culture of fear and a search for truth. In light of these developments, Drane presents a case for a more practical theology, a reinvigorated style of ministry, and a restatement of classic Christian beliefs for the twenty-first century. - Publisher.
Culture -- Community -- Mission -- Ministry -- Theology.
Includes bibliographical references (p. [155]-160) and indexes.
Keywords: Church renewal